Labour and struggle : glimpses of Chinese history. (Peking : China Welfare Institute, 1960)
Bibliotheek Camille Huysmans
Supplement bij 'China reconstructs', april 1960
Engels
Brochure
Keywords: communistische pers; arbeidersgeschiedenis; China